An Althusserian Reading of Harold Pinter’s One for the Road - Aydoğdu, Merve (Journal of History Culture and Art Research, 2014)
Louis Althusser in his seminal essay Ideology and Ideological State Apparatuses in Lenin and Philosophy and Other Essays (1970) discusses the ways through which a State dominates/subjugates its subjects by means of Repressive and Ideological State Apparatuses, the effects of which are traceable in Harold Pinter's 1984-play One for the Road. Within this scope, this paper seeks to examine Pinter's one-act play from an Althusserian point of view with a view to demonstrating the manipulative influence of ISAs and SA on the creation of subjects who would serve for the State.